2019
DOI: 10.1097/bsd.0000000000000897
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Cervicothoracic Junction in Cervical Arthrodesis Results in Lower Rates of Adjacent Segment Disease Without Affecting Operative Risks or Patient-Reported Outcomes

Abstract: Study Design: Retrospective cohort study. Objective: To evaluate the risks and benefits of crossing the cervicothoracic junction (CTJ) in cervical arthrodesis. Summary of Background Data: Whether the CTJ should be crossed in cervical arthrodesis remains up for debate. Keeping C7 as the distal end of the fusion risks adjacent segment disease (ASD) and can result in myelopathy or radiculopathy. Longer fusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…Prior clinical studies have shown conflicting results when comparing the extent of multilevel PCF constructs 4–7,16–20. Osterhoff et al5 showed no difference in radiographic outcomes in a retrospective analysis comparing posterior constructs ending at C7 versus T1 and T2.…”
Section: Discussionmentioning
confidence: 99%
“…Prior clinical studies have shown conflicting results when comparing the extent of multilevel PCF constructs 4–7,16–20. Osterhoff et al5 showed no difference in radiographic outcomes in a retrospective analysis comparing posterior constructs ending at C7 versus T1 and T2.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies 10,34,35 have shown that crossing the CTJ prevents kyphotic collapse, ongoing neck pain, and symptomatic adjacent segment degeneration. According to the results of this study, CTJ should be avoided if possible; if CTJ must be included, fusion extension up to T2-4 can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, DJK and kyphosis occurred because of the destruction of the unique mechanical structure and muscle degeneration at the CTJ after the extension of fusion to C7/T1, which is thought to exacerbate postoperative neck pain (Figure 5). Some studies 10,34,35 have shown that crossing the CTJ prevents kyphotic collapse, ongoing neck pain, and symptomatic adjacent segment degeneration. According to the results of this study, CTJ should be avoided if possible; if CTJ must be included, fusion extension up to T2-4 can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A hypothesized protective effect of the extension of the construct across the CTJ is thought to rely on a more rigidity provided by inclusion of the thoracic spine. Conversely, a construct ending at C7 make the involved cervical segments act as a single column leaning over the rigid thoracic spine with only a single interposed disc, thus subjected to signi cant mechanical stress that may result in early disc degeneration [24]. In a biomechanical study Cheng et al [7] reported that in posterior cervical instrumentations, the intradiscal pressure of the lower adjacent disc was signi cantly lower for instrumentations that crossed the CTJ.…”
Section: Rods Constructsmentioning
confidence: 99%
“…The published 'in vivo' studies however provide contrasting evidences. Articles by Schroeder et al [41], Ibaseta et al [24] and Fayed et al [15] found that posterior cervical constructs ending at C7, have increased risks of adjacent segment disease, while Huang et al [22] and Lee et al [32] found no signi cant increase in adjacent segment disease when stopping the construct at C7. At the same time, instrumentations that cross the CTJ have been reported to be associated with increased operative times and intraoperative blood loss [15,22].…”
Section: Rods Constructsmentioning
confidence: 99%